Address workshop “Chica Chica Boom of the 21st century”: a pratical experience (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
This article is part of the EBA/UFRJ. Master's in Design research, on the subject “Carmen Miranda's costume design: visual identity, culture and design”. The aim of this paper is to show how the study of the theatrical elements, through the construction of props for the costumes, can be fundamental for the formation of the artistic and technical work of the indumentary EBA/UFRJ student. The classroom becomes part of this student's effectiveness, bringing significant experiences in the professional training process to the labor market. Based on research, technical visits, creation and development of costume projects, the future costume designer appropriates real experiences of execution and the entire construction process. With this purpose, we use the concepts of Design associated with the Performing Arts, as we understand the similarity of their elaborations and constructions in terms of design methodology to guide us in this paper.
Keywords: Design; costume design; education